Comparison of Ultrasound Guided Optic Nerve Sheath Diameter Measurements with Other Cranial Imaging Methods (Cranial Computed Tomography and Magnetic Resonance Imaging) in Pediatric Intensive Care Patients - Burcu Dadı; Emel Uyar; Ruslan Asadov; Feyza İnceköy Girgin; Gazanfer Ekinci; Nilüfer Yalındağ Öztürk (Galenos Yayinevi, 2019)
Introduction:Optic nerve sheath diameter (ONSD) measurements aid in diagnosis of increased intracranial pressure (ICP). Computed tomography (CT) and magnetic resonance imaging (MRI) are commonly used modalities for detecting ICP. Lately, ONSD measurements via ultrasound (US) are getting popular as an alternative method due to the ease of performance at the bedside and repeatability. Our study objective was to investigate whether US measurements correlated with CT/MRI counterparts.Methods:This was a single-center, prospective study. All intubated patients aged 1 month-18 years with a cranial CT/MRI for any indications, who could be scanned ultrasonographically, were included after parental consent. Optic nerve US was performed by a single investigator. CT/MRI ONSDs were measured by a neuro-radiologist. Data obtained from US and CT/MRI scans were compared.ResultsA total of 94 different measurements were obtained. The mean ONSD in US and CT was 4.56±0.66 cm and 4.65±0.72cm on the right side, whereas the mean left ONSD was 4.52±0.63 cm and 4.46±0.67 cm, respectively (p=0.4). Correlation coefficient for right ONSD was r=0.448 (p=0.002) while it was r=0.448 (p=0.001) for left ONSD. Both CT and US measurements showed a linear increase, and the correlation between them was moderate. A subgroup of 8 patients who had less than 5 hours between their central imaging and US scan showed strong correlation between measurements for both right and left ONSD [r=0.774, (p=0.024) and r=0.811 (p=0.014), respectively].Conclusion:There was a correlation between US and CT/MRI ONSD measurements in our study. The correlation was stronger when the time interval was less than 5 hours between measurements. Our findings suggest that US may be a useful, reliable and cost-effective method for assessment and clinical follow-up of increased ICP in intubated pediatric intensive care unit patients.